Carbon nitride based Schottky junction with a Ni–Mo synergistic interaction for highly efficient photocatalytic hydrogen production. Issue 21 (16th September 2022) - Ding, Lei; Wang, Li-Jing; Liu, Ru-Yi; Li, Yan-Fei; Sun, Hai-Zhu
Abstract : A CN/3NiMoP2 Schottky junction with a Ni–Mo synergistic interaction demonstrates a comparable photocatalytic HER performance to CN/3 wt% Pt and satisfactory stability. Abstract : It remains a great challenge to develop low cost cocatalysts with comparable performance to noble metals for photocatalytic hydrogen evolution. Herein, in situ growth of nanosized bimetallic phosphides NiMoP2 on graphite carbon nitride (CN) is realized. The synergistic interaction between Ni and Mo and the intimate CN/3NiMoP2 Schottky junction greatly accelerates the separation of photogenerated charge carriers and the extraction from CN, as well as maintain the stability of H2 production. The optimized CN/3NiMoP2 achieves a more advantageous H2 yield of 783 μmol g −1 h −1 and a corresponding apparent quantum efficiency of 3.9% at 420 nm, which are much better than that of CN and 3NiMoP2 composite that is synthesized via non- in situ methods (CN–3NiMoP2 ), indicating the importance of Schottky junction formation via the in situ preparation method. More importantly, CN/3NiMoP2 demonstrates a comparable photocatalytic hydrogen production performance to CN/3 wt% Pt (770 μmol g −1 h −1 ) and satisfactory stability (21 h). This work provides a new route to synthesize low-cost cocatalysts that are expected to replace Pt in the field of photocatalytic hydrogen production.